1996
DOI: 10.1007/bf02053806
|View full text |Cite
|
Sign up to set email alerts
|

Early results of laparoscopic surgery for colorectal cancer

Abstract: A laparoscopic approach to colorectal cancer results in early outcome after treatment that is comparable with conventional therapy for colorectal cancer. A randomized trial is needed to compare long-term outcomes of open and laparoscopic approaches with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(28 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…General surgical and gynecologic literature provides several examples of abdominal wall metastases after laparoscopic procedures [23, 24]. However reviewing major series from these specialties shows no difference in tumor recurrence rates in wounds or the abdominal wall [25, 26].…”
Section: Pneumoperitoneummentioning
confidence: 99%
“…General surgical and gynecologic literature provides several examples of abdominal wall metastases after laparoscopic procedures [23, 24]. However reviewing major series from these specialties shows no difference in tumor recurrence rates in wounds or the abdominal wall [25, 26].…”
Section: Pneumoperitoneummentioning
confidence: 99%
“…A fairly uniform finding among reported series is that laparoscopic colorectal procedures almost invariably take longer than the comparable open procedure [12, 46,56,57,58,59]. The operating times are reduced with progress along the learning curve, and, importantly, they may approach the surgeon’s own times for the corresponding open procedure.…”
Section: Discussionmentioning
confidence: 86%
“…Port-site herniation can be largely prevented by the meticulous closure of all port sites >10 mm. Operative complications such as major haemorrhage, inadvertent enterotomy, ureteral injury, and major vessel laceration have all been reported, with rates ranging from 0 to 12% [6, 12, 14, 46, 51, 56, 57, 59]. The overall morbidity rate is between 6 and 39% [59,68,69,70,71,72,73,74,75,76,77].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard procedures were right hemicolectomy, left hemicolectomy, anterior resection and abdominoperineal resection. The extent of adequate radical surgery may be a major problem of laparoscopic surgery, but recent series including retrospective and prospective registries as well as comparative studies have clearly demonstrated that oncologic principles are not compromised by laparoscopic techniques, and yield of lymph nodes, surgical margins (proximal, distal, and radial), and length of bowel resected were comparable to open cancer surgery [12][13][14][15][16][17][18][19][20][21]. To determine definitely whether laparoscopic resections for colorectal cancer can provide adequate oncologic surgery, several multicenter prospective randomized trials are currently underway.…”
Section: Oncologic Radicalitymentioning
confidence: 99%